Bacterial Aetiology of Acute Infectious Conjunctivitis and their Antimicrobial Susceptibility Pattern - Khan, Md Iqram Ul Azam; Chowdhury, Md Hasnat Jaki; Chowdhury, Md Ashiqur Rahman; Himi, Nazia Ahmed; Mashreki, Shams; Chowdhury, Ajmin Huda Chowdhury; Ahmed, Md Sharfuddin (Medicine Today, 2026)
Introduction: Pathogenic microorganisms cause ocular disease and the most frequently affected parts of the eye are the conjunctiva, lid and cornea. Conjunctivitis is the most common cause of “red eye”. The major bacterial causes of conjunctivitis are Staphylococcus aureus, Streptococcus pneumoniae, Klebsiella spp, Haemophilus influenzae. It was evident that the irrational use of antibiotics has greatly increased the antibiotic resistance of eye-infecting bacteria and is turning the issue into a serious challenge for the fight against bacterial infections. Objectives: To isolate and identify the bacterial pathogens in acute infectious conjunctivitis and to observe their antimicrobial susceptibility pattern. Materials and Methods: This cross sectional study was carried out in the Department of Community Ophthalmology and Department of Microbiology & Immunology, Bangladesh Medical University (BMU) during March, 2021 to August, 2022. A total of 75 patients with the age of 10 years and above diagnosed clinically as a case of acute bacterial conjunctivitis were included in this study. All isolated organisms were tested for their in vitro antimicrobial susceptibility against various antibiotics using the Kirby-Bauer disk diffusion method. All the information was recorded in data collection sheets and analysed using SPSS and Microsoft Excel. Results: In this study, 26.7% cases had culture positive and 73.3% culture negative. Staphylococcus aureus (30.0%) was the most common organism. The isolates showed the maximum antibiotic sensitivity to moxifloxacin (75.0%) and gentamicin (75.0%) and the lowest to azithromycin (25.0%). Conclusion: Accurate diagnosis of the type of infection and its etiologic factors and prescription of suitable antibiotics may shorten the duration of the disease as well as transmission time. Medicine Today 2026, Vol.38 (1): 76-81